PENGALAMAN PEREMPUAN DENGAN HIV/AIDS DALAM MENJALANI PENGOBATAN - Agusdila ' Safitri; Yulia Irvani Dewi; Erwin ' ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract This study was qualitative research with descriptive women living with HIV/AIDS. The purpose of this study was to describe experience of women who have HIV/AIDS in doing treatment. Five participants were selected by purposive sampling method. Data were collected by in-depth interview which completed by field note and analyzed by Colaizzi method. This study identified five major themes: patients who have HIV/AIDS had been blood test, counseling and ARV treatment, participants in doing treatment, motivations for doing a treatment, supporting for women with HIV/AIDS and wisheses of participants. The study recommends to health care provider specially for nurse who should increasing support to physiological and psychological ARV treatment and patient for keep doing HIV/AIDS treatment. Keywords: HIV/AIDS, women experience, treatment